If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8a + 4 = 2a + 4 Reorder the terms: 4 + 8a = 2a + 4 Reorder the terms: 4 + 8a = 4 + 2a Add '-4' to each side of the equation. 4 + -4 + 8a = 4 + -4 + 2a Combine like terms: 4 + -4 = 0 0 + 8a = 4 + -4 + 2a 8a = 4 + -4 + 2a Combine like terms: 4 + -4 = 0 8a = 0 + 2a 8a = 2a Solving 8a = 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. 8a + -2a = 2a + -2a Combine like terms: 8a + -2a = 6a 6a = 2a + -2a Combine like terms: 2a + -2a = 0 6a = 0 Divide each side by '6'. a = 0 Simplifying a = 0
| 10(2a-3b)-1(4b-2a)= | | 19-4+5-16= | | 3-8x-16x^4=0 | | (3x/4)=2 | | 3x+5yi=8-i | | f(x)=tan(cos(2x)) | | (5x/6)=0 | | 5/3x=2/3x+1/3 | | -1/8z=-5.5 | | x+14=171 | | (-3/5)m=12 | | hj-2h+5g+4f-20= | | 3y-4=6 | | -16x^2-7x+10=0 | | 2.38=48 | | -16x^2-7x-1=0 | | 5(2w+3)10w=6(4w+1) | | 4+-2v+12=-8 | | x^2-36/2x-12 | | 2(1+3s)-4=6s-2 | | d=3m | | 6+3+2+2= | | (-b/3)=6 | | 5-(f+3)=5f | | 91=-4(6-6b)-5 | | 2ln(x)=ln(21) | | 17=32 | | 40=16t^2+88t | | 20=(1/4c) | | 75=3x^2-9 | | 18x+5=20x+1 | | log*(x+11)-log(2)=log*(5x+1) |